An iron-carboxylate bond links the heme units of malaria pigment. - Slater, A F (1991)
The intraerythrocytic malaria parasite uses hemoglobin as a major nutrient source. Digestion of hemoglobin releases heme, which the parasite converts into an insoluble microcrystalline material called hemozoin or malaria pigment. We have purified hemozoin from the human malaria organism Plasmodium falciparum and have used infrared spectroscopy, x-ray absorption spectroscopy, and chemical synthesis to determine its structure. The molecule consists of an unusual polymer of hemes linked between the central ferric ion of one heme and a carboxylate side-group oxygen of another. The hemes are sequestered via this linkage into an insoluble product, providing a unique way for the malaria parasite to avoid the toxicity associated with soluble heme.